Development and Reliability of a Street Skateboarding Notational Analysis Framework and Application - Shelley N. Diewald; Niklas Noth; Nick Mancini; Jonathon Neville; John Cronin; Matt R. Cross (Applied Sciences)
Notational analysis (NA) systems are regularly used to quantify sports performance but have not been adopted in competitive skateboarding. In this study, we aimed to develop an NA application to quantify outcome-related aspects of skateboarding judging criteria (trick selection, obstacle selection, and execution), leveraging known skatepark obstacles and trick classification from public broadcast footage (60 Hz) of the Tokyo 2020 Olympic Men’s and Women’s semi-finals. We also assessed the intra- and inter-rater reliability of frame selection for key trick attempt events—take-off, event (obstacle interaction) start and end, and landing. Frame selection from 593 trick attempts (male = 324, female = 269) were found reliable (mean absolute difference (MAD) < 3 frames) by a single, experienced rater. Take-off (MAD: intra-rater = 1.43, inter-rater = 3.82 frames) and landing frame (MAD: intra-rater = 1.33, inter-rater = 1.55 frames) were more reliably selected than obstacle interaction (MAD: Inter = 2.04–2.26, Inter = 3.62–4.35 frames), attributed to obstacle and trick type. Generally, trick attempts over longer durations appeared less reliable, but still within useable limits; as such, the NA approach used in this study could be used for describing and understanding performance in elite street skateboarding.